Identification of ANLN as ETV6 partner gene in recurrent t(7;12)(p15;p13): a possible role of deregulated ANLN expression in leukemogenesis. Issue 1 (December 2015) - Campregher, Paulo; Pereira, Welbert; Lisboa, Bianca; Puga, Renato; Helman, Ricardo; Miyagi, Mariana; da Mata, Evelyn; Datoguia, Tarcila; Velloso, Elvira; Bacal, Nydia; Ross, Jeffrey; Ali, Siraj; et al.
Abstract TheETV6 gene encodes an ETS family transcription factor that is involved in a myriad of chromosomal rearrangements found in hematological malignancies and other neoplasms. A recurrentETV6 translocation, previously described in patients with acute myeloid leukemia (AML) (Genes Chromosomes Cancer 51:328–337, 2012, Leuk Res 35:e212-214, 2011), whose partner has not been identified is t(7;12)(p15;p13). We herein report that the t(7;12)(p15;p13) fusesETV6 toANLN, a gene not previously implicated in the pathogenesis of hematological malignancies, and we demonstrate that this translocation leads to high expression of the fusion transcript in the myeloid and lymphoid lineages.